Application of Power Matrix Technique for Controlling DFIG Wind Turbine System - S. Jabeer Basha; Loveswara Rao Burthi (Institute of Advanced Engineering and Science, 2015)
With advance in usage of wind turbine technologies, as compared with other renewable sources the cost of wind turbine becomes competitive. Due to this economic problem, other disadvantages and by considering the global warming, the utilization of wind turbine has increased since last decade. For maintain the active power at constant, the use of Doubly-Fed Induction Generators with Energy Storage System like super capacitor (or) batteries can be used, with a two layer control scheme. This paper presents a novel concept for controlling doubly fed induction generator called power transfer matrix. This power transfer matrix technique is designed based on the instantaneous values of active and reactive power of the system. In order to protect the DFIG during fault conditions a matrix converter scheme based power/current controller is presented.